Towards Translation of PqsR Inverse Agonists: From In Vitro Efficacy Optimization to In Vivo Proof‐of‐Principle (Adv. Sci. 5/2023). Issue 5 (14th February 2023) - Hamed, Mostafa M.; Abdelsamie, Ahmed S.; Rox, Katharina; Schütz, Christian; Kany, Andreas M.; Röhrig, Teresa; Schmelz, Stefan; Blankenfeldt, Wulf; Arce‐Rodriguez, Alejandro; Borrero‐de Acuña, José Manuel; Jahn, Dieter; Rademacher, Jessica; et al.
Abstract : Quorum Sensing Inhibitor In article number 2204443, Martin Empting and colleagues describe the medicinal‐chemistry‐driven discovery of a new quorum sensing inhibitor (QSI) against Pseudomonas aeruginosa . The discovered QSI synergized with standard‐of‐care antibiotic tobramycin in a murine infection model providing an in vivo proof‐of‐concept.